The effectiveness of the use of the task-based learning approach (tbl) to reinforce eighth graders ’ english oral production at Centro Escolar Católico san Lorenzo, Santa Ana, during the year 2020 - Aguirre Chámul, Gerson David; Henríquez Henríquez, Rosa Marilena; Hernández Herroes, Tatiana Elizabeth; Hernández Rivas, Sandra Jeamileth (2024)
Learning and teaching English as a second language is crucial, especially at Centro Escolar Católico San Lorenzo, Santa Ana, where eighth graders are not producing English as expected. Pupils are not capable of communicating in English orally in an effective way; this was observed and measured through a diagnosis carried out by the research team that identified and described such a problematic situation